A STUDY ON ECONOMIC AND ENVIRONMENTAL BENEFITS OF CONSTRUCTION AND DEMOLITION WASTE RECYCLING (CAHIERS MAGELLANES-NS, 2024)
The construction industry is one of the largest producers of waste globally, contributing significantly to environmental degradation and resource depletion. The study on recycling C&DW sheds light on creative solutions for building activities that reduce environmental impacts and establish a circular economy model within the construction sector. The importance of recycling and reusing construction and demolition wastes (C&DW) is crucial for the building industry to provide a solid foundation for incorporating a circular economy into its operations. This demonstrates the replacement of C&DW (Construction and Demolition Waste) with conventional construction materials, which are similar in size and possess significant environmental advantages. Reaching this stage in disclosing these findings to the developers, it is undeniable that these results hold great significance for a building industry that aims to minimize material usage and reduce waste. This study consists of conservation-friendly heritage support and allows the construction industry to move to a more environmentally friendly future.